Workspace Disorder Does Not Influence Creativity and Executive Functions - Manzi, Alberto; Durmysheva, Yana; Pinegar, Shannon K.; Rogers, Andrew; Ramos, Justine (Frontiers in Psychology, 2019)
Recent research by Vohs, Redden and Rahinel (2013) garnered media attention after reporting that disordered environments increase creativity. The present research was designed to conceptually replicate and extend this finding by exploring the effect of workspace disorder on creativity. Participants were randomly assigned to work at a neatly organized (Order condition) or a messy desk (Disorder condition), where they completed several paper-and-pencil and computerized tasks, including two validated creativity measures (Abbreviated Torrance Test for Adults; ATTA; Goff & Torrance, 2002; Alternative Uses Task; adapted from Guilford, 1967). We also included several executive control measures from the NIH EXAMINER (Kramer, 2011), to explore the role of reduced top-down control in explaining a possible creativity-disorder connection. Independent-samples t-tests failed to replicate any significant difference in creativity between the Order and Disorder conditions. Furthermore, the conditions did not differentially affect executive control. Despite implementing an experimental setup similar to the one in Vohs et al. (2013), including a larger sample size, and adopting multiple measures of the constructs of interest, we did not find any effect of workspace clutter on cognitive performance. At this stage, the relationship between disorder and cognition seems elusive and does not warrant the claims it generated in the popular press.